Vaginal wall cysts in a prepubertal girl: a case report - Zahra Basirat; Masoumeh Golsorkhtabaramiri (Babol University of Medical Sciences, 2015)
A vaginal cyst is an encapsulated sac, situated on or under the lining of vagina, and contains liquid or semi liquid substance. Vaginal cysts have rarely proved to be more troublesome than causing a bit of discomfort and slight pain, but in some cases, they can develop into tumors. A 5-year-old girl, who was complaining about a weird pain in her lower abdomen, was referred to the gynecology center of the hospital. Ultrasonography revealed a vague large cyst in her uterus and vagina. Surgical procedure was necessary to remove it. The patient was followed up for 6 months, and no sign of recurrence of the cyst was observed.